Effect of Pistacia palaestina Boiss. Essential Oil on Colorectal Cancer Cells: Inhibition of Proliferation and Migration. Issue 1 (2nd January 2020) - Awwad, Oriana; Alabbassi, Reem; Abaza, Ismail F.; Coperchini, Francesca; Rotondi, Mario; Chiovato, Luca; Afifi, Fatma U.
Abstract: Colorectal cancer (CRC) is the third most common malignancy diagnosed worldwide and its management is still challenging; necessitating discovery of alternative agents. Natural compounds have historically been used in the treatment of CRC. Pistacia genus has recently received particular interest for its antitumor activity. The present study aimed to analyze the qualitative and quantitative composition of P. palaestina Boiss. fruit oil obtained from trees grown in Jordan, and to investigate its anticancer activity on CRC cells. The essential oil was obtained by hydro-distillation and solid phase micro-extraction (SPME). The composition of the essential oils were determined by gas chromatography-mass-spectrometry (GC/MS) and gas chromatography-flame ionization detector (GC/FID) analyses. The anticancer activity of P. palaestina fruit essential oil was investigated on HCT116 CRC cells. The cytotoxic activity was performed by MTT assay while the wound-healing assay was conducted to examine the potential anti-migratory activity of the fruit oil. The levels of CXCL8 were also measured in the cells' supernatant through ELISA. Monoterpene hydrocarbons were detected as the main constituents in the hydro-distilled and in the SPME detected oils with 96.1 % and 98.3 %, respectively. The MTT assay showed that P. palaestina fruit oil significantly reduced HCT116 cells viability and potentiated the anti-cancer activity of the traditional chemotherapy, 5-FU. An anti- migratory effect was observed on HCT116 cells after treatment with the fruit oil. P. palaestina significantly reduced CXCL8 levels, a chemokine contributing in CRC cells proliferation, and metastasis. The results of the study demonstrate P. palaestina as a promising alternative or adjuvant therapy for the treatment of CRC.